2020
DOI: 10.1037/xlm0000777
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potentials reveal increased dependency on linguistic context due to cognitive aging.

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 95 publications
(240 reference statements)
0
1
2
Order By: Relevance
“…Some authors found that the latency of the N400 effect of older participants was delayed with decreasing performance at a reading span task to assess working memory [ 25 ]. However, there was no association between reading span and the size of the N400 effect in this study, nor with N400 amplitude measures in two other studies [ 45 , 46 ]. Some studies also reported associations between N400 amplitude measures and verbal fluency (tasks that combined phonological and semantic fluency) or vocabulary [ 45 , 46 ].…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Some authors found that the latency of the N400 effect of older participants was delayed with decreasing performance at a reading span task to assess working memory [ 25 ]. However, there was no association between reading span and the size of the N400 effect in this study, nor with N400 amplitude measures in two other studies [ 45 , 46 ]. Some studies also reported associations between N400 amplitude measures and verbal fluency (tasks that combined phonological and semantic fluency) or vocabulary [ 45 , 46 ].…”
Section: Discussioncontrasting
confidence: 93%
“…However, there was no association between reading span and the size of the N400 effect in this study, nor with N400 amplitude measures in two other studies [ 45 , 46 ]. Some studies also reported associations between N400 amplitude measures and verbal fluency (tasks that combined phonological and semantic fluency) or vocabulary [ 45 , 46 ]. Thus, there is a possibility that working memory, executive functions and/or lexical processing might explain some individual variability in the N400 ERP.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In la Roi et al's (2020) study, performance on the Verbal Fluency task significantly predicted participants' N400 and P600 amplitudes, indicating that the mechanisms underlying verbal fluency play a role in the use of context in literal and idiomatic sentence processing. La Roi et al ( 2020) also carried out a Dutch Reading Span task (Van Den Noort et al, 2008) to measure working memory capacity, and a Dutch version of the Paired-Associates task (Shimamura et al, 1995) to measure inhibition skills.…”
Section: The Present Studymentioning
confidence: 82%
“…In a previous study, la Roi et al (2020) used ERPs to compare younger and elderly adults' processing of literal and idiomatic sentences in context. They found that 1) both younger and elderly adults showed facilitated processing of idiomatic relative to literal sentences, consistent with findings from previous studies (e.g., Beck & Weber, 2020;Canal et al, 2015;Carrol & Littlemore, 2020;Laurent et al, 2006;Rommers et al, 2013;Titone & Connine, 1999), 2) elderly adults were as able as younger adults to use context to facilitate the retrieval of word meanings in both literal and idiomatic sentences, and 3) elderly adults, but not younger adults, relied on context information for the subsequent integration of these word meanings in the sentence.…”
Section: Using Erps To Investigate Effects Of Cognitive Aging On Sent...mentioning
confidence: 99%